Getting through the day: a pilot qualitative study of U.S. women's experiences making decisions about anti-nausea medication during pregnancy - Marlaine Figueroa Gray; Clarissa Hsu; Linda Kiel; Sascha Dublin (BMC, 2018)
Abstract Background Nausea during pregnancy affects 80% of pregnant women and can severely affect women's functioning and quality of life. Women often have difficulty deciding whether to take anti-nausea medications due to concern about medication risks. This paper foregrounds U.S. women's voices as they share their experiences making decisions about anti-nausea medication use. Methods As a pilot study, we conducted two focus groups including 20 women who had filled at least one prescription for an anti-nausea medication during pregnancy. Topics included deciding about and taking anti-nausea medications. Transcripts were analyzed by two medical anthropologists using an inductive or open coding approach. Results Women in our pilot study carefully considered whether to take anti-nausea medications. Most women preferred not to take medications, in general, but were willing to do so for severe symptoms. When considering medications, they expressed concerns about risks to fetal health. They considered information from internet research, their health care provider, and the experiences of friends and family. While some women in our study decided against taking medications, many did take a prescription medication, and they reported substantial improvement in their symptoms and sense of well-being. Conclusions Women weighed various sources of evidence to assess the risks and benefits of taking anti-nausea medication and ultimately made a range of choices. More research is needed about the effectiveness and risks of anti-nausea medication, to help support women in their decision-making process, and also about the best methods to communicate scientific evidence to women.